Outside Back Cover: Volume 3 Issue 4. Issue 4 (20th December 2022) - Pu, Jie; Gao, Yong; Cao, Qinghe; Fu, Gangwen; Chen, Xing; Pan, Zhenghui; Guan, Cao
Abstract : Outside back cover image : The cover image represents V‐MOF nanowire‐derived multifunctional fibers (V‐MOF NWs@CNT fibers) for simultaneous use in various energy storage and utilization applications. The fiber‐shaped integrated sensing system can be woven into textiles to monitor human activities, and the energy supply system can also drive the water‐splitting unit, proving that V‐MOF NWs@CNT fibers have promising potential for building high‐performance multifunctional integrated electronics. (DOI: https://doi.org/10.1002/smm2.1088 )